Large-scale synthesis of α-amino acid-N-carboxyanhydrides. Issue 1 (2nd January 2017) - Semple, J. Edward; Sullivan, Bradford; Sill, Kevin N.
ABSTRACT: Hetero- and homopolymers prepared fromα -amino acid- N -carboxyanhydrides (NCAs) monomers are widely useful products. The preparation of pure NCA monomers has been extensively studied in the past. Purification methods including repeated crystallizations, extraction, and flash column chromatography have been devised. However, these methods are not easily amendable to large-scale NCA preparations. This article describes the synthesis of numerous highly purified NCAs on a >100 g scale using a simple filtration step through diatomaceous earth (celite). The resulting NCAs provided polyethylene glycol (PEG)–amino acid triblock polymers devoid of low-molecular-weight by-products that were routinely observed when unfiltered batches of NCAs were used. Also disclosed is the preparation of NCAs at ambient temperature. Traditionally, NCA reactions using a phosgene source are heated. This study shows these reactions can be driven by the slight exotherm that forms upon reagent mixing. This eliminates the need for an external heating source, simplifying large-scale reactions. GRAPHICAL ABSTRACT: